Radix Rehmanniae Extract Ameliorates Experimental Autoimmune Encephalomyelitis by Suppressing Macrophage-Derived Nitrative Damage - Li, Wenting; Wu, Hao; Gao, Chong; Yang, Dan; Yang, Depo; Shen, Jiangang (Frontiers in Physiology, 2018)
Multiple sclerosis (MS) is a neuroinflammatory disease in central nervous system (CNS) without effective treatment or medication yet. With high prevalence of MS patients worldwide and poor therapeutic outcome, seeking novel therapeutic strategy for MS is timely important. Radix Rehmanniae (RR), a typical Chinese Medicinal herb, has been used for neuroinflammatory diseases in Traditional Chinese Medicine for centuries. However, scientific evidence and underlying mechanisms of RR for MS are unclear. In this study, we tested the hypothesis that RR could attenuate the progress and severity of MS via suppressing macrophage-derived nitrative damage and inflammation by using experimental autoimmune encephalomyelitis (EAE) model for mimicking MS pathology. The results showed the RR treatment effectively ameliorated clinical disease severity, inhibited inflammation/demyelination in spinal cord and alleviated CNS infiltration of encephalitogenic T cells and activated macrophages. Meanwhile, RR possessed bioactivities of scavenging ONOO- and reducing the expression of iNOS and NADPH oxidases in the spinal cords of the EAE mice. Furthermore, RR treatment suppressed nuclear factor-κB (NF-κB) signaling pathway in the splenocytes of EAE mice. The in vitro experiments on macrophages and neuronal cells exerted consistent results with the in vivo animal experiments. Taken together, we conclude that Radix Rehmanniae extract has therapeutic values for ameliorating EAE/MS pathological process and disease severity and its underlying mechanisms are associated with anti-inflammation and inhibiting macrophage-derived nitrative damages. Further study could yield novel promising therapeutic agent for multiple sclerosis.